Development of Digital Comic KOMA (Komik Majas) for Teaching Personification in the Fourth Grade of Elementary School - Setiawan, Riki Bayu; Cahyaningtyas, Andarini Permata (UNDIKMA, 2025)
Learning media is an important thing that really helps teachers in learning activities. This research is motivated by the lack of innovative media in Indonesian language learning activities on the material of personification. This study aims to describe the development process, feasibility, and effectiveness of KOMA (Komic Majas) media. This research is included in the type of research and development (R&D) with the ADDIE model and a quantitative approach. Data were obtained from teachers, students, documents, and experts. Data collection was conducted through test methods in the form of pretests and posttests, as well as non-test methods such as interviews, questionnaires, and documentation. To test the validity of the data, item analysis was used. Data analysis included a normality test and a paired t-test. KOMA (Komik Majas) media obtained a very feasible score from the material expert of 90% and from the media expert of 93%. The student response questionnaire showed a result of 92%, while the teacher response questionnaire amounted to 95%. The results of the paired t-test showed that the development of KOMA (Komik Majas) media significantly improved the understanding of personification of fourth-grade students of SD Negeri Podorejo 03.